Problem-Solving Dalam Pendidikan Islam - Arlina Arlina; Miftahul Jannah Ira; Rini Nurwana Saragih; Fadhila Khairani; Mardih Putri Jerohmi (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2023)
Thinking is an activity that cannot be separated from humans, as well as being the most substantial differentiator between humans and other creatures. This study aimed to analyze thinking and problem-solving in Islamic education. From this research, it is hoped that a concept will be born that can be used to solve the problems of Islamic education. The focus of this study discusses the thought process, problem-solving and the factors that influence it as well as the steps of problem-solving. This focus will be fully directed in the context of Islamic education. This research uses literature study techniques using primary sources in the form of authoritative books and journals. The results of this study showed that in the context of Islamic education, it was well realized that there were many problems that cause the lagging of Islamic educational institutions. It was very important to think of the right way to get out of the problem immediately by using the right problem-solving principle. In addition, the managers of educational institutions must work together and seriously implement the principles of Islamic teachings as a solution to answer these problems. Keywords: Thinking, Problem Solving, Islamic Education